Numerical study of tides in the Malacca Strait with a 3-D model. Issue 9 (September 2020) - Haditiar, Yudi; Putri, Mutiara R.; Ismail, Nazli; Muchlisin, Zainal A.; Ikhwan, Muhammad; Rizal, Syamsul
Abstract: Malacca Strait (MS) has an important role and potential for many countries. It is a major transportation route for oil and commodities across continents. In addition, various activities such as shipping, fishing, aquaculture, oil drilling, and energy are also carried out in MS. Tides strongly affect the MS environment so that it becomes a major parameter in MS management. This paper is the first study, which presents MS tidal hydrodynamics based on a baroclinic and nonhydrostatic approach. Tidal hydrodynamics in MS and the surrounding waters were assessed using tidal forces, temperature, salinity, and density. This study analyzes the amplitude, phase, current ellipses, and semi-major axis of the tides. These variables are obtained from the simulation results of the three-dimensional numerical models of M2 tides and combined tides (M2, S2, N2, K1, and O1) with nonhydrostatic models. Then the results obtained are verified by observation data. Amplitude and phase of the tidal wave in MS originate from two directions, namely the northern part of MS (Andaman Sea) and the South China Sea (SCS). Tides from the north of MS propagate into the MS, while tides from the SCS travel to Singapore Waters (SW) and the south of MS. This causes a complex residual flow in SW and shoaling in the middle of MS. Shoaling in the middle of MS is characterized by a large amplitude and semi-major, as in B. Siapiapi. The results of this analysis show that tidal waves are dominated by semidiurnal types rather than diurnal types. The M2 current ellipse has dominantly anticlockwise rotation along the west of the MS, while along the east of MS, it has generally a clockwise rotation. Abstract : Oceanography, Computational mathematics, Earth Sciences, Environmental science, Geophysics, Three-dimensional model, M2 tides, semidiurnal tides, tidal circulation, Singapore Waters, South China Sea.